1990
DOI: 10.1093/jnci/82.24.1918
|View full text |Cite
|
Sign up to set email alerts
|

Results of Stereotactic Brachytherapy Used in the Initial Management of Patients With Glioblastoma

Abstract: Recent studies have shown a survival benefit for patients with recurrent glioblastomas treated with stereotactic brachytherapy. On the basis of these encouraging results, we began a prospective study in 1987 to evaluate the use of brachytherapy in patients with newly diagnosed glioblastoma. Patients were considered eligible for this study if they met the following criteria: Karnofsky performance status 70% or greater; tumor size not greater than 5 cm in any dimension; a radiographically well delineated, suprat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…20,47 Across the world Gamma Knife (Elekta AB) stereotactic radiosurgery (SRS) has been used as an adjuvant therapy in more than 40,000 patients with glial neoplasms. Although prior retrospective studies have documented a modest survival advantage with the addition of SRS delivered using various technologies, 14,23,24,27,29,32,34,39 others have found no added benefit. 4,9,16,37,38 A single prospective randomized trial by the Radiation Therapy Oncology Group (RTOG 93-05) 42 found no improvement in overall survival (OS) when various forms of linear acceleratorand Gamma Knife-based SRS were given prior to conventional fractionated RT.…”
mentioning
confidence: 99%
“…20,47 Across the world Gamma Knife (Elekta AB) stereotactic radiosurgery (SRS) has been used as an adjuvant therapy in more than 40,000 patients with glial neoplasms. Although prior retrospective studies have documented a modest survival advantage with the addition of SRS delivered using various technologies, 14,23,24,27,29,32,34,39 others have found no added benefit. 4,9,16,37,38 A single prospective randomized trial by the Radiation Therapy Oncology Group (RTOG 93-05) 42 found no improvement in overall survival (OS) when various forms of linear acceleratorand Gamma Knife-based SRS were given prior to conventional fractionated RT.…”
mentioning
confidence: 99%
“…Over the years, radiation treatment has been refined, going from whole brain radiation to more localized and higher dose radiation to the excised tumor bed and 2 cm surrounding it. The concept of direct implantation of radioactive seeds into the tumor bed has also been evaluated, but this has not shown significant therapeutic advantages [23]. Since prognosis in GBM patients is still grim, death usually precedes the onset of side effects: in fact, cognitive deficit secondary to radiation is rare within the first year after treatment and the majority of patients only experience transient malaise and general weakness [24].…”
Section: Current Treatment For Glioblastomamentioning
confidence: 99%
“…[5,10,32,34,39,45,59,65] This approach is usually combined with the assessment of conventional measures such as survival duration, time to relapse, and imaging-documented changes in tumor size. [12,13,18,28,35] The toxicity of therapy has also been assessed, for the most part, in categorical terms such as "major" or "minor" morbidity and mortality.…”
Section: Validity and Quality Of Life Assessment In Neurooncologymentioning
confidence: 99%
“…[34] As a result of these findings there is now increasing use of primary postoperative chemotherapy and deferred radiation therapy in children with medulloblastoma. [51] Multidimensional QOL considerations have also prompted deferred radiation therapy in the management of cerebral low-grade glioma.…”
Section: Multidimensional "Profile" Qol Measurementmentioning
confidence: 99%